European Society of Gynaecological Oncology quality indicators for surgical treatment of cervical cancer - Cibula, David; Planchamp, François; Fischerova, Daniela; Fotopoulou, Christina; Kohler, Christhardt; Landoni, Fabio; Mathevet, Patrice; Naik, Raj; Ponce, Jordi; Raspagliesi, Francesco; Rodolakis, Alexandros; Tamussino, Karl; et al. (International journal of gynecological cancer, 2020)
BACKGROUND: Optimizing and ensuring the quality of surgical care is essential to improve the management and outcome of patients with cervical cancer.To develop a list of quality indicators for surgical treatment of cervical cancer that can be used to audit and improve clinical practice. METHODS: Quality indicators were developed using a four-step evaluation process that included a systematic literature search to identify potential quality indicators, in-person meetings of an ad hoc group of international experts, an internal validation process, and external review by a large panel of European clinicians and patient representatives. RESULTS: Fifteen structural, process, and outcome indicators were selected. Using a structured format, each quality indicator has a description specifying what the indicator is measuring. Measurability specifications are also detailed to define how the indicator will be measured in practice. Each indicator has a target which gives practitioners and health administrators a quantitative basis for improving care and organizational processes. DISCUSSION: Implementation of institutional quality assurance programs can improve quality of care, even in high-volume centers. This set of quality indicators from the European Society of Gynaecological Cancer may be a major instrument to improve the quality of surgical treatment of cervical cancer.
Keywords: ženské pohlaví; Uterine Cervical Neoplasms; směrnice pro lékařskou praxi jako téma; Quality Indicators, Health Care; Female; chirurgická onkologie; gynekologické chirurgické výkony; lidé; Surgical Oncology; Humans; ukazatele kvality zdravotní péče; Practice Guidelines as Topic; nádory děložního čípku; Gynecologic Surgical Procedures